"Halal tourism": is it the same trend in non-Islamic destinations with Islamic destinations?. Issue 2 (1st February 2020) - Jia, Xiong; Chaozhi, Zhang
ABSTRACT: Halal tourism is a young research area, especially in non-Islamic context. This research aims to explore Muslim tourists' needs and tourism practitioners' responses in China. Based on 32 interviews, the findings show that Muslim tourists' needs include six aspects, namely food, hotel, transportation, entertainment and shopping, toilet, and service staff. In terms of religious-related needs, they only demand for halal food, water-friendly toilets and prayer facilities. Yet, while Chinese tourism practitioners hold positive attitudes towards receiving Muslin tourists, they only provide halal food. This research suggests halal tourism attributes developed in Islamic countries cannot be applied to non-Islamic countries.